种航空发动机构件表面残余应力电磁场调控方法 (2019)
本发明公开了种航空发动机构件表面残余应力电磁场调控方法，包括以下步骤：在常温下对新制的航空发动机构件进行电磁场调控处理，处理时间为3～600s，所述电磁场由交变磁场和脉冲电场耦合而成，交变磁场的强度为500～30000A/m，交变磁场的频率为1～1000Hz，脉冲电场的最大峰值电流为5～20000A，脉冲电场的脉冲周期为0.01～1.0s。本发明取消了传统喷丸工艺，利用电磁场调控构件材料表层及近表层残余应力分布，可以提高制造精度和表面粗糙度，缩短工艺流程，降低制造成本和周期。 The invention discloses an electromagnetic field regulation and control method of surface residual stress of an aero-engine component. The regulation and control method comprises the following step: performing electromagnetic field regulation and controlling on the new-made aero-engine component at normal temperature for 3-600s, wherein the electromagnetic field is formed by coupling an alternating magnetic field and a pulsed electric field; the intensity of the alternating magnetic field is 500-30,000A/m; the frequency of the alternating magnetic field is 1-1,000Hz; the maximum peak current of the pulsed electric field is 5-20,000A; the pulse period of the pulsed electric field is 0.01-1.0s. According to the method, the traditional shot blasting process is canceled, and t